2016
DOI: 10.1038/srep38849
|View full text |Cite
|
Sign up to set email alerts
|

STRAP Acts as a Scaffolding Protein in Controlling the TLR2/4 Signaling Pathway

Abstract: The WD40-repeat protein serine/threonine kinase receptor-associated protein (STRAP) is involved in the regulation of several biological processes, including cell proliferation and apoptosis, in response to various stresses. Here, we show that STRAP is a new scaffold protein that functions in Toll-like receptor (TLR)-mediated immune responses. STRAP specifically binds transforming growth factor β-activated kinase 1 (TAK1) and IκB kinase alpha (IKKα) along with nuclear factor-κB (NF-κB) subunit p65, leading to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…FAs also influence multiple intracellular processes through mechanisms that include the activation of peroxisome proliferator‐activated receptor (PPAR)α and PPAR gamma coactivator 1 α (PGC‐1α), leading to the upregulation of genes involved in FA metabolism and the biogenesis of peroxisomes and mitochondria. Reports have suggested that excessive FAs might augment inflammation through activation of toll‐like receptor (TLR) signalling and following activation of nuclear factor kappa‐light‐chain enhancer of activated B‐cells (NF‐κB) . There is increasing evidence that FA availability is an independent predictor of metabolic disorders including insulin resistance and T2DM .…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%
“…FAs also influence multiple intracellular processes through mechanisms that include the activation of peroxisome proliferator‐activated receptor (PPAR)α and PPAR gamma coactivator 1 α (PGC‐1α), leading to the upregulation of genes involved in FA metabolism and the biogenesis of peroxisomes and mitochondria. Reports have suggested that excessive FAs might augment inflammation through activation of toll‐like receptor (TLR) signalling and following activation of nuclear factor kappa‐light‐chain enhancer of activated B‐cells (NF‐κB) . There is increasing evidence that FA availability is an independent predictor of metabolic disorders including insulin resistance and T2DM .…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%
“…Despite the clinical implications of lipid accumulation in the heart (Poirier et al, 2006; He et al, 2017; Anstee et al, 2018; De Coster et al, 2018), the underlying molecular mechanisms are poorly understood. A major limitation could be due to the complexity associated with the involvement of multiple signaling pathways which include: (1) direct modulation of ion channel function by FFAs, and (2) FFA activation of the toll-like receptor (TLR) and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) leading to secretion of pro-inflammatory cytokines (Huh et al, 2016) and subsequent cardiac electrical remodeling. Previous reports have demonstrated that FFAs increase inflammation (Lundman et al, 2007), while genetic knockdown of TLR is protective in mice fed a high-fat diet rich in palmitate (Davis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The in situ functions of most ELDs remain elusive, although some domains have been characterized in model systems. Putative functions of these domains include the disruption of phagocytosis (Lee et al, 2002;Nguyen et al, 2014;Reynolds and Thomas, 2016), regulation of gene expression (Viboud and Bliska, 2005), host cell entry (Bierne and Cossart, 2002), cell death, differentiation, signaling, and immune response (Wall and Mccormick, 2014;Huh et al, 2016;Miller et al, 2016), or roles as antioxidants, nutrients, or cofactors (McIntire, 1998;Choi et al, 2008). The FNT3 domainenriched in Latescibacteria -may facilitate extracellular cellulose degradation (Kataeva et al, 2002), consistent with metabolic analyses of Latescibacteria (Farag et al, 2017).…”
Section: Eukaryotic-like Domains (Elds) and Signatures Of Host-associmentioning
confidence: 57%